ANALISIS KETEPATAN KODE DIAGNOSIS PENYEBAB DASAR KEMATIAN BERDASARKAN ICD-10 DI RS PANTI RAPIH YOGYAKARTA - , TRIAN HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Determination of the basic code cause of death is very important to have it done correctly mortality and deadly diseases preventive measures can be implemented optimally. Determination of the underlying cause of death diagnosis codes are determined by the coding staff expertise in coding and doctorâs compliance in filling out the cause of death according to the rules. Rules that are used to determine the diagnosis of the underlying cause of death codes are based on ICD-10 with the help of Determination Manual Code Cause of Death According to the ICD-10 as well as MMDS tables as auxiliary table. Objective: To determine the implementation of the determination of the underlying cause of death diagnosis code in Panti Rapih Hospital of Yogyakarta, the percentage accuracy of the diagnosis of the underlying cause of death codes, and the factors that led to inaccuracies basic cause of death codes. Methods: This study used a descriptive method with qualitative approach and a cross-sectional study design. Subjects in this study were coding staff, doctors, and Chief of Medical Record Installation, while the object of this study is the Death Registration Statement Panti Rapih Hospital of Yogyakarta in 2012. Techniques of collecting data through observation, interviews, and documentation. Results: Implementation of basic coding causes of death in Yogyakarta Rapih Panti not fully in accordance with the ICD-10, coding staff cause of death diagnosic encodes only one written by a doctor. Sequence of the disease to death that is right has a percentage of 69.59% with the correct UCoD at 97.48% and uncorrect UCoD 2.52%, while the sequence of disease to death that is not appropriate for 30.41% with the appropriate UcoD for 38.46% and 61.54% are not appropriate. Total procentage accuracy of UCoD for 79.53% and that is not for 20, 47%. The factors that lead to inaccuracies because the code base is not the death of the SPO basic coding cause of death, has not been used as a MMDS table is used as a hospital-owned facility for coding staff, not all physicians complete diagnosis of the basic cause of death, and the absence of coding audit or evaluation of the basic cause of death code accuracy. Keywords: Code, Analysis, Code Cause of Death